Conservação da Polpa de Frutas Vermelhas por Métodos Combinados - Carvalho, Kellen Cristina Masaro (2012)
The techniques for preserving food, can maintain a large number of natural characteristics of the fruit, making storage and marketing viable for a longer period than what could be achieved with the raw product. The aim of this study was to evaluate the quality of the pulp of red fruits with different concentrations of potassium sorbate. The experiment was conducted at the Federal Institute of Education, Science and Technology in southern Minas Gerais - Campus Machado, using three pulps that were formulated with equal amounts of each fruit (blackberry, raspberry and strawberry) crushed the proportion of sucrose used was 1/6 and water 1/6 with respect to the total mass of crushed red fruits. The heat treatment was 100 ° C for 10 minutes. The concentration of potassium sorbate used was 0%, 0.05% and 0.1%. After cooling, the pulps were packaged in plastic containers containing 150 mL. The packages containing the pulps were sealed, identified and stored at 25 ° C in BOD incubator for 60 days. The microbiological, chemical and physical performed every 30 days, were as follows: yeast and mold, coliforms at 35 º C and 45 º C, analysis of Salmonella sp, vitamin C, pH, titratable acidity, soluble solids, color analysis (values L *, a *, b *, C * and h °). The experiment was conducted in a completely randomized design (CRD) with three replications. Treatments were arranged by a 3 x 3 factorial, being constituted by factors concentration of potassium sorbate (0%, 0.05% and 0.1%) and storage time (0, 30 and 60 days), respectively. The experimental plot consisted of a plastic satisfaction 150 mL of red fruit pulp. The pulp of red fruits with no added potassium sorbate stored at 25 º C for 30 days showed a count of yeasts and molds above the limit specified by Brazilian law. The red fruit pulps treated with 0.05% and 0.1% potassium sorbate were enough to ensure the stability of physical, chemical and microbiological during the 60 days of storage at 25 ° C. As the red fruit pulps with addition of 0.05% and 0.1% potassium sorbate have substantially similar results it is recommended to use in production of the fruit pulp red adding 0.05% potassium sorbate as preservative Red fruit pulp for economy product. Results were subjected to analysis of variance, after the comparison test of means, with a statistically significant difference of 5%.